2017
DOI: 10.1080/15287394.2017.1367097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenylethanoid glycosides, derived from Herba cistanche, on cognitive deficits and antioxidant activities in male SAMP8 mice

Abstract: Cognitive deficits are closely associated with hippocampal synaptic changes. Phenylethanoid glycosides (PhG), derived from Herba cistanche, are known to exert protective effects on cognitive deficits in Alzheimer's disease (AD); however, the underlying mechanisms of this herbal extract on cognitive performance remain unclear. The aim of this study was thus to examine the protective mechanism attributed to PhG on cognitive deficits in an AD senescence accelerated mouse prone 8 (SAMP8) model. Cognitive deficit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…[11][12][13] Deng et al found that the echinacoside, one of the major active compounds of cistanche, exhibited protective effects on TNF-α-induced SH-SY5Y cell apoptosis. 16 For instance, Zhang et al investigated one of the cistanches extractions and confirmed its function of extending lifespan. There are two main flows by which the cistanches scavenge the free radicals, namely directly involving in the removal of free radicals or blocking their production and regulating the antioxidant enzymes related to the free radical metabolism in vivo, such as SOD, CAT and GPX.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Deng et al found that the echinacoside, one of the major active compounds of cistanche, exhibited protective effects on TNF-α-induced SH-SY5Y cell apoptosis. 16 For instance, Zhang et al investigated one of the cistanches extractions and confirmed its function of extending lifespan. There are two main flows by which the cistanches scavenge the free radicals, namely directly involving in the removal of free radicals or blocking their production and regulating the antioxidant enzymes related to the free radical metabolism in vivo, such as SOD, CAT and GPX.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were conducted in China and published between 2001 and 2017, of which 4 studies were published in English [33, 42, 45, 49]. In total, 1696 rats or mice were involved, and the sample size ranged from 40 to 192.…”
Section: Resultsmentioning
confidence: 99%
“…The Morris water maze test, including the spatial test and the probe test, was conducted in 11 studies [32, 33, 38-41, 43, 45, 47-49]. All 11 studies reported the spatial test using the escape latency as an outcome measure, of which 3 studies [33, 48, 49] provided graphic data, and we failed to apply digital ruler software or to get in touch with the author for further information.…”
Section: Resultsmentioning
confidence: 99%
“…PhGs were found to improve cognitive deficits in SAMP8 mice by improving synaptogenesis and synaptic plasticity. 98 It has been reported that the mean lifespan of Caenorhabditis elegans was extended by 13.64% and 15.82% after treated with 200 and 300 μM echinacoside, respectively. The protective effect of echinacoside on Aβ-induced toxicity in C. elegans was almost equal to that of ginkgolide A, a well-known agent with positive effects for AD.…”
Section: Neuroprotective Effectmentioning
confidence: 99%